‘DEDUCTIO IN DOMUM MARITI’ A ZAWARCIE ‘IUSTUM MATRIMONIUM’ - Benincasa, Zuzanna (Zeszyty Prawnicze, 2016)
‘DEDUCTIO IN DOMUM MARITI’ AND THE CONCLUSION OF A ‘IUSTUM MATRIMONIUM’ Summary According to the communis opinio the classical Roman law did not have a formal procedure of concluding a marriage, since its conclusion required only the mutual consent of a man and a woman (affectio maritalis, consensus). Nonetheless, the Roman culture developed a number of ritual acts related to the conclusion of a marriage, most of them deeply rooted in the Roman tradition and history and of great symbolic significance. The central moment of a wedding ceremony appears to be the deductio in domum mariti i.e. the ritual bringing of the bride to her husband’s house. The significance of this ritual is reflected in language since the expression uxorem ducere (“to lead a wife”) is the most common Latin expression for “to marry,” also in the legal sense, since according to some jurists when deductio in domum mariti had been accomplished, the couple was considered duly and legally married. The main function of the deductio was thus to give a proof that the marriage had been concluded and to manifest mutual affectio maritalis. Deductio in domum mariti played a special role when a marriage was concluded inter absentes (it seems that only the groom person could be absent and not the bride). In this case the formal deductio ceremony seems to have been an indispensable act constituting the only way in which the mutual affectio maritalis could be expressed. Since the bride’s procession to her new husband’s house was considered the public declaration of the consensus necessary to conclude a legal marriage, if the groom was absent such a ceremony was necessary as a proof that mutual affectio maritalis had been expressed and thus the marriage had been concluded. Nonetheless the necessity of leading the bride to her husband’s home in the case of a matrimonium inter absentes should not be confused with the constitutive character of deductio in domum mariti. Consensus still remained the only constitutive element and deductio in domum mariti was only the formal way in which this consensus had to be expressed in the particular circumstances.